The G-8 Debt Cancellation Proposal and Its Implications for the Fund : Further Considerations. (Policy Papers; Policy Paper, 2005)
The G-8 has proposed that the Fund, the International Development Association, and the African Development Fund cancel 100 percent of their claims on countries having reached, or upon reaching, the completion point under the enhanced Heavily Indebt Poor Country (HIPC) Initiative. The proposal was initially presented to the G-8 Finance Ministers' Conclusions on Development issued on June 11, 2005, and reaffirmed in the statement on Africa signed by G-8 Heads of State and Government at the Gleneagles Summit on July 8, 2005.